Borophene as an anode material for Ca, Mg, Na or Li ion storage: A first-principle study - Mortazavi, Bohayra; Dianat, Arezoo; Rahaman, Obaidur; Cuniberti, Gianaurelio; Rabczuk, Timon (Journal of power sources, 2016)
Borophene, the boron atom analogue to graphene, being atomic thick have been just recently experimentally fabricated. In this work, we employ first-principles density functional theory calculations to investigate the interaction of Ca, Mg, Na or Li atoms with single-layer and free-standing borophene. We first identified the most stable binding sites and their corresponding binding energies as well and then we gradually increased the ions concentration. Our calculations predict strong binding energies of around 4.03 eV, 2.09 eV, 2.92 eV and 3.28 eV between the borophene substrate and Ca, Mg, Na or Li ions, respectively. We found that the binding energy generally decreases by increasing the ions content. Using the Bader charge analysis, we evaluate the charge transfer between the adatoms and the borophene sheet. Our investigation proposes the borophene as a 2D material with a remarkably high capacity of around 800 mA h/g, 1960 mA h/g, 1380 mA h/g and 1720 mA h/g for Ca, Mg, Na or Li ions storage, respectively. This study can be useful for the possible application of borophene for the rechargeable ion batteries. [Display omitted] •We studied the application of borophene for the rechargeable ion batteries.•Borophene presents a remarkably high capacity for Mg, Na or Li ions storage.•Ions diffusion on the borophene are fast with low energy barriers.